2016
DOI: 10.4103/0970-9290.183116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electron-beam irradiation on antimicrobial, antibiofilm activity, and cytotoxicity of mouth rinses

Abstract: The E-beam irradiation enhanced the antibiofilm activity of mouth rinses without modifying the cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The previous study done by Mohanakumari [37], any antimicrobial agents are expected to have minimal cytotoxic effect on host cells. This previous study results demonstrated the cytotoxic effect of both CP and LS on cultured HGF [38].…”
Section: Discussionmentioning
confidence: 96%
“…The previous study done by Mohanakumari [37], any antimicrobial agents are expected to have minimal cytotoxic effect on host cells. This previous study results demonstrated the cytotoxic effect of both CP and LS on cultured HGF [38].…”
Section: Discussionmentioning
confidence: 96%